2016
DOI: 10.1519/jsc.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peer Influence on Exercise Behavior and Enjoyment in Recreational Runners

Abstract: Fitness professionals and popular media sources often recommend exercising with a partner to increase exercise motivation, adherence, intensity, and/or duration. Although competition with peers has been shown to enhance maximal athletic performance, experimental research examining the impact of peer influence on submaximal exercise behavior in adults is limited. The purpose of this study was to determine the effects of the presence of familiar and unfamiliar peers, vs. running alone, on recreational runners' v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…*Significant main effect for travel direction (p˂0.05); † Significant interaction between travel direction and interaction between travel direction, day and time of day (p˂0.05). 1 EAST significantly different to WEST (p˂0.05); 2 Significantly different to (p˂0.05); 4 Significantly different to all other days (p˂0.05); 5 Significantly different to day 2 and 3 (p˂0.05); 7 Significantly different to (p˂0.05); 8 Significantly different to day 1 (p˂0.05). a Large ES for EAST different to WEST (d˃0.90); b Large ES for difference to c Large ES for difference to all other days (d˃0.90); d Large ES for difference to day 1 and 2 (d˃0.90); e Large ES for difference to Large ES for difference to day 2 and 3 (d˃0.90).…”
Section: Declarationsmentioning
confidence: 97%
See 1 more Smart Citation
“…*Significant main effect for travel direction (p˂0.05); † Significant interaction between travel direction and interaction between travel direction, day and time of day (p˂0.05). 1 EAST significantly different to WEST (p˂0.05); 2 Significantly different to (p˂0.05); 4 Significantly different to all other days (p˂0.05); 5 Significantly different to day 2 and 3 (p˂0.05); 7 Significantly different to (p˂0.05); 8 Significantly different to day 1 (p˂0.05). a Large ES for EAST different to WEST (d˃0.90); b Large ES for difference to c Large ES for difference to all other days (d˃0.90); d Large ES for difference to day 1 and 2 (d˃0.90); e Large ES for difference to Large ES for difference to day 2 and 3 (d˃0.90).…”
Section: Declarationsmentioning
confidence: 97%
“…Data presented as mean ± SD and range (minimum -maximum). Significant main effect for travel direction (p˂0.05); † Significant interaction between travel direction and 1 EAST significantly different to WEST (p˂0.05); 2 EAST significantly different to BASE & WEST (p˂0.05); different to all other days (p˂0.05);4 Significantly different to day of arrival (p˂0.05);5 Significantly different to (p˂0.05). a Large ES for EAST different to WEST (d˃0.90); b Large ES for EAST and WEST different to BASE ( c Large ES for WEST different to BASE; d Large ES for difference to all other time points (d˃0.90).…”
mentioning
confidence: 99%
“…In diabetic patients prescribed resistance exercise, the presence of additional individuals in the exercise environment has been shown to be facilitative (34). Conversely, in other type of exercise, such as individual endurance activities, the use of social situation effects has been shown to have no influence on self-determined running duration, speed or post exercise ratings of exertion (RPE), during recreational running (11). Interestingly however, when a competitor is present during time trial cycling, performance improvements have been observed, as a result of external attentional focus mediated reductions in perceptions of effort (39).…”
Section: Introductionmentioning
confidence: 99%
“…As described by Carnes (2014), showing recognition to the runners benefits them to achieve the desired goals or behavior is called "Social support". The influence of social support helps in influencing the devotion to exercise, exercise intentions, the effectiveness of exercise, and the behavior concerning exercise (Carnes, 2014).…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…As described by Carnes (2014), showing recognition to the runners benefits them to achieve the desired goals or behavior is called "Social support". The influence of social support helps in influencing the devotion to exercise, exercise intentions, the effectiveness of exercise, and the behavior concerning exercise (Carnes, 2014). Therefore, it is considered useful to interact with other people to help explore the effect of it during training sessions, as well as in their enjoyment of other exercises, and to increase the motivation of an athlete during exercise (Carnes, 2014).…”
Section: Intrinsic Motivationmentioning
confidence: 99%